Validation of screening tool for diagnosis of childhood asthma by exclusion method - Kondekar, Santosh; Dange, Nimisha; Rathi, Surbhi (Indian Journal of Child Health, 2022)
Introduction: In the 21st century, with growing concerns over over-diagnosis of asthma in children; the diagnosis of asthma is left as diagnosis by exclusion. On the same lines, an attempt had been made to device a criteria to exclude diagnosis of asthma. The criteria are labeled as other than asthma (OTA) criteria. It is assumed that if a case does not satisfy OTA tool, then it is likely to be asthma. This study had objectives of validation of screening tool by expert and validation of OTA tool by direct application on patients. Materials and Methods: This was an observational and prospective study only. Total 120 cases were enrolled. Questionnaire applied on all cases and all of the 120 cases were followed up on day 30 with clinical diagnosis and were included in results estimation. Results: According to the screening tool, out of 120 cases, 83 cases (69.2%) were found to have OTA while 37 cases (30.8%) werefound to have non-OTA. However, among this study population, 94 cases (78.3%) had non-asthma and 26 cases (21.7%) had clinical diagnosis of asthma taken as gold standard. The association between clinical diagnosis and total score based diagnosis was found to bestatistically significant (p=1.96E-07). Sensitivity was 91.57% and specificity was 51.35% which helps detect OTA cases effectively. Predictive value of positive test is 80.85% and predictive value of negative test was 73.08%. OTA category has relative risk of 3.003 for diagnosis of non-asthma as compared to 0.262 for non-OTA category being almost 3 times in comparison to non-OTA category. Thus, OTA was consistent with non-asthma diagnosis. Conclusion: On direct application of patients in prospective study, this tool has proven its value as an effective screening tool. This was the first such study to diagnose asthma by exclusion, devising a criterion for other than asthma conditions.